Kadar Hormon LH Basal sebagai Prediktor Kebrhasilan Stimulasi Ovarium pada Program Bayi Tabung - Ariantini, Dyah; Lutfi, Mohammad; Hadiati, Diah Rumekti (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Ovarian stimulation is part of assisted reproductive technology (ART) process, which aims to spur the growth of follicles to be developed, so that it will increase the chance of getting pregnant. LH surge cause the final follicular maturation, ovulation and becoming corpus luteum. So that an increase in LH may adversely affect the development of the follicle and eventually affect in-vitro fertilization.Objective To determine the effect of basal LH hormone to follicles on the stimulation of ovarian.Method: Cohort Retrospective. Research Location: Permata Hati Clinic of Sardjito Hospital, YogyakartaResult dan Discussion: The study included 70 cycles of 70 women who underwent ovarian stimulation for in-vitro fertilization and fulfill inclusion and exclusion criterias. The subjects were divided into 2 groups based on basal LH hormone levels i.e. LH ≤ 3 mIU/ml as the test group and LH >3 mIU/ml as the control group. From analysis, response to ovarian stimulation in group with LH ≤3 mIU/ml was significantly different than LH >3 mIU/ml (RR 1,875; 95% CI 1,275–2,757; p=0,00*).Conclusion: Low level of basal LH (≤ 3 mIU/ml) generating fewer number of mature follicles in patients who performed ovarian stimulation in in-vitro fertilization program.Keyword: basal LH, ovarian stimulation, in-vitro fertilization.